Not all toxic butterflies are toxic: high intra- and interspecific variation in sequestration in subtropical swallowtails - Dimarco, Romina Daniela (2017)
Many herbivorous insects make use of plant secondary metabolites by consuming and storing these toxic compounds in their body tissue or integument, thereby obtaining chemical defense against their natural enemies. Swallowtail butterflies in the tribe Troidini (Papilionidae) sequester toxic alkaloids (aristolochic acids, AAs) from their host plants in the genus Aristolochia. Troidine butterflies have been a model group for development of theory on host plant chemical sequestration, but most studies on this group have been limited to a single species in North America. These studies have led, in part, to the paradigm that troidine butterflies are toxic, thereby explaining the numerous mimicry relationships that exist throughout most of their range. Herein, we present one of the first comparative studies in a single location of a community of troidine butterflies. We examined the AA content of five co-occurring troidine butterfly species and their two Aristolochia host plants. We found that one Aristolochia species, A. triangularis, was preferred in choice assays and did not possess quantifiable levels of AA. We also found that most troidine butterflies did not possess quantifiable levels of AAs, but larvae have the ability to sequester AAs when it is present in their diet. A larval preference experiment showed that host plant AA concentration did not influence larval feeding choice. A performance experiment showed that higher levels of AAs in the diet increased larval mortality, which might indicate a cost associated with sequestration of the chemical defense and also might shed some light on why so many troidine butterflies in this community have little or no AAs. We propose that automimicry might be operating in this system and many putative models of this paradigmatic system might not possess plant-derived defensive chemistry.